Validação farmacológica do óleo essencial de Rosmarinus officinalis L. (alecrim) : atividades antiinflamatória e analgésica - Faria, Lucimari Romana Dipe de (2005)
The Rosmarinus officinalis L (rosemary) is widely used in popular medicine The objective of this paper was o study the essential oil of this species (ROEO) on inflammatory and hyperalgesic models in vivo in order to detect the possible involvement of its active principles on the inflammatory and algesic responses and analyze its ulcerogenic potential The following experimental models were used rat paw edema granuloma test vascular permeability ear erythema by croton oil writhing test in mouse formalin test hot plate and gastric ulcer by stress The yield of the essential oil extracted by hydrodestilation of the aerial parts from Rosmarinus officinalis was 1.4% With the oral administration in rats and mice of the doses (50 100 200 500 1000 2000 and 5000 mg/kg) it was not possible to determine the median lethal dose (LD50) With the oral doses of 50 100 200 and 300 mg/kg on the rat paw edema the ROEO produced dose-dependent effect of which the lineal correlation coefficient was r = 0.9986 (y = -13.93 + 0.30) and the median effective dose (ED50) was 212 mg/kg In the writhing test in mice the oral doses of ROEO 10 50 100 200 300 and 400 mg/kg produced dose-dependent effect with a correlation coefficient of r = 0.93095 (y = 30.54 + 0.073) and ED50 of 261 mg/kg The daily administration of ROEO (300 mg/kg, orally) for 6 days inhibited the granulomatous tissue formation in 59% (p <0.001 Student t test) In the ear erythema by croton oil the ROEO in the oral dose of 300 mg/kg provoked the significant inhibitory effect of 77% (p <0.05) In the vascular permeability test the oral treatment with ROEO antagonized the response to histamine thus inhibiting the vascular permeability in 50% (p <0.05, Student t test) The oral treatment with ROEO (300 mg/kg) inhibited phase I of the hyperalgesic process by formalin in 40% (p <0.05 Student t test) while phase II was inhibited in 48% In the hot plate test ROEO (300 mg/kg, orally) produced more latency times than basal times the difference however was not significant In the gastric ulcer trial the ROEO-treated group inhibited in 44% the number of gastric lesions by stress when compared with the control group The results suggest that ROEO shows antiinflammatory activity in both acute and chronic inflammatory processes exhibits analgesic activity and provokes little harmful interference on the gastric mucosa